Функційно-комунікативні ознаки стверджувальної / заперечної модальності - Костусяк, Наталія Миколаївна (My University, 2013)
In the article assertive/negative modality as a grammeme of category of syntactic modality is systematically described, and ts parameter values are outlined; the basic types of designs with assertive and negative modality are characterized, predicate components that structure expression of this kind are singled out, and central and peripheral equipment of formal expression are accentuated.
Keywords: надкатегорія модальності; синтаксична модальність; морфологічна модальність; лексико-граматична модальність; стверджувальна / заперечна модальність; предикат